Efikasi Herbisida Isopropilamina Glifosat Dalam Mengendalikan Gulma Perkebunan Karet (Hevea Brasiliensis) Belum Menghasilkan - Hendi Pamungkas; Dad R.J. Sembodo; Rusdi Evizal; Hidayat Pujisiswanto (Politeknik Negeri Lampung., 2018)
Rubber (Hevea brasiliensis) is an important plantation crop in Indonesia because its products are used as raw material for rubber industry and source of stock-exchange. The existence of weeds on the rubber land causes competition of growing facilities and affect the growth of rubber plants. One of the most common herbicide active ingredients that used to control immature plant weeds is isopropylamine glyphosate. This research aims to (1) find out the dose of isopropylamine glyphosate herbicide that effectively control weeds in immature rubber cultivation, (2) to know the change of weed’s composition due to the application of isopropylamine glyphosate herbicide, (3) to know whether the phytotoxicity of rubber plants occurs due to isopropylamine glyphosate herbicide application. This research was conducted in smallholder rubber plantation in Marga Agung Village, Jati Agung Subdistrict, South Lampung Regency and Weed Laboratory of Agriculture Faculty of Lampung University from November 2016 until March 2017. This research used randomized block design (RAK) with four replicates and six treatment levels dose of herbicide isopropylamine glyphosate herbicide 796,5 g/ha (P1), 1062 g/ha (P2), 1327.5 g/ha (P3), 1593 g/ha (P4), mechanical weeding (P5), and without restraint/control (P6). The homogeneity of various data was tested by Bartlett test, the data additivity was tested by Tukey test, and the difference of median treatment was tested by Least Significant Different (LSD) test at 5% level. The results showed that: (1) isopropylamine glyphosate herbicide dose 796,5 – 1593 g/ha effectively controlling total weeds, grass weeds up to 12 weeks after application and nut grass weeds up to 4 weeks after application, and dose 1593 g/ha effectively controlling leaf weeds up to 8 weeks after application, (2) dose 1327,5 – 1593 g/ha effectively controlling Ottochloa nodosa weeds up to 12 weeks after application and Commelina diffuse up to 4 weeks after application, (3) dose 796,5 – 1593 g/ha effectively controlling Cyperus brevifolius weeds up to 4 weeks after application, and doses of 1593 g/ha effectively controlling Asystasia gangetica weeds up to 8 weeks after application, (4) doses of 796,5 – 1593 g/ha resulted in changes in weed’s composition at 4, 8, and 12 weeks after application, (5) doses 796,5 – 1593 g/ha does not poison the rubber plant.